Insufficiency of Vitamin D in adolescents of the South of Brazil - William, Cordeiro de Souza; André, de Camargo Smolarek; Luis, Paulo Gomes Mascarenhas (International Journal of Bone and Mineral Metabolism, 2018)
This article examines vitamin D insufficiency among adolescents in southern Brazil. It summarizes prevalence, potential determinants such as sun exposure and diet, and implications for bone health, calling for targeted prevention and screening strategies.